An innovative technique for the extraction and stability of polyphenols using high voltage electrical discharge - Leila Abbaspour; Nazila Ghareaghajlou; Mohammad Reza Afshar Mogaddam; Zahra Ghasempour (Current Research in Food Science)
Polyphenols are the main group of phytochemicals with several biological activities. Due to the adverse effects of conventional solvent extraction methods, innovative extraction techniques have been used as alternatives to overcome these problems. High voltage electric discharge (HVED) is an eco-friendly innovative extraction technique based on the phenomenon of electrical breakdown in water. This technique induces physical and chemical processes, leading to product fragmentation, cellular damage, and liberation of bioactive compounds. HVED treatment can extract polyphenols at lower temperatures and shorter times than the conventional solvent extraction methods. This review summarizes the effect of HVED processing parameters on the recovery and stability of polyphenols from plant sources. Hydroethanolic solutions improve the HVED-assisted extraction of polyphenols compared to water. Moreover, acidic solvents are suitable for the high recovery and protection of polyphenols during electric discharges. This study revealed the efficacy of the HVED technique in extracting polyphenols for their utilization in the food and pharmaceutical industries.